Pengaruh Kombinasi Titik Lokal Dan YNSA Terhadap Penurunan Derajat Nyeri Pada Pasien Nyeri Pinggang (Low Back Pain) - Sri Yatmihatun; Sholichan Badri; Suwaji Handaru Wardoyo (Poltekkes Kemenkes Surakarta, 2019)
Background: Low Back Pain is a common disorder involving the muscles, nerves and spine. The use of combination acupuncture, namely the local point and Yamamoto News Scalp Acupuncture (YNSA) is expected to accelerate the decrease in pain in patients with Low Back Pain. Methods: This study is used 45 respondents divided into 3 treatment groups, namely 1) Local point acupuncture therapy group, 2) Yamamoto News Scalp Acupuncture acupuncture therapy group, and 3) Local point combination with Yamamoto News Scalp Acupuncture therapy group. This research was conducted in the working area of the Ngemplak Community Health Center, Boyolali from January 2017 to September 2017. Measurement of pain using Visual Analog Scale (VAS). Results: The evaluation results showed that the respondent's data is normally distributed and homogeneous. ANOVA test showed there was a significant relationship between the local point acupuncture therapy group, Yamamoto News Scalp Acupuncture (YNSA) and Combination. The F value in this study is smaller than α (0.05). The T test showed that local acupuncture therapy is more effective than Yamamoto acupuncture therapy. News Scalp Acupuncture, and point combination acupuncture therapy are more effective than local points. Conclusion: Therfore it is the first report that proved the better method of combination (Local Point and YNSA) for reducing LBP quickly.